Three new species of Sarasaeschna Karube & Yeh, 2001 (Odonata: Anisoptera: Aeshnidae) from northeastern India; with a new record of Sarasaeschna khasiana (Lieftinck, 1968) - Joshi, Shantanu; Sawant, Dattaprasad; Pawar, Ujwala; Khan, Fahim; Gassah, Rejoice; Ismavel, Vijay Anand; Kunte, Krushnamegh (Zootaxa, 2026)
We erect three new species of Sarasaeschna Karube & Yeh, 2001 (Odonata: Anisoptera: Aeshnidae): Sarasaeschna dosdewaensis sp. nov., S. nuboides sp. nov. and S. sigotaayo sp. nov., and provide a new record of S. khasiana (Lieftinck, 1968) based on specimens collected from northeastern India. We illustrate male caudal appendages of all Sarasaeschna and provide taxonomic keys to males (n=20) of all Sarasaeschna spp.